Some Fresh Water Algae of Oil Refinery Effluent Drains of Assam, India - Baruah, P.P.; Kakati, B.; Ahmed, I. (Our Nature, 2010)
The present paper deals with the morpho-taxonomic account of some hitherto unknown fresh water algal species of hydrocarbon polluted refinery drains of Assam. Twenty two taxa of class Chlorophyceae, Bacillariophyceae, Euglenineae and Cyanophyceae were identified from three effluent drains of Guwahati Oil Refinery. Cyanophyceae with 11 species was the dominant algal group in the study sites and Oscillatoria was the dominant genus with 8 species. Key words: Fresh water algae, Oscillatoria, oil refinery effluent, Assam DOI: 10.3126/on.v7i1.2561 Our Nature (2009) 7:139-145